A New Method of Treatment of Temporomandibular Joint Ankylosis with Osteodistraction Using the Sh-Device: A Case Report - Gholamreza Shirani; Mahnaz Arshad; Xaniar Mahmoudi (Tehran University of Medical Sciences, 2018)
This case report presents a 16-year-old boy with bilateral temporomandibular joint (TMJ) bony ankylosis due to trauma. The patient had undergone several unsuccessful therapeutic surgeries and was experiencing reduced mouth opening, difficulty in eating and speaking, poor oral hygiene, snoring, and depression. Bilateral gap arthroplasty and distraction osteogenesis (DO) were performed. After the surgery, we were able to move the osteodistractors forward and prevent the upward and backward movement of the proximal mandibular segment with the use of our custom-made Sh-device, which allowed bone growth and soft-tissue matching. The mandibular deficiency was treated, and the patient's sleep quality significantly improved after three months. The physical, orthodontic and speech therapies were continued. The facial asymmetry, difficulty in sleeping, eating and speaking, and low self-esteem were completely resolved. At the 8-year follow-up, the patient's condition was satisfactory. The Sh-device can be used as a contemporary treatment modality for TMJ ankylosis.